Rapid recovery from catastrophic paraneoplastic anti-NMDAR encephalitis secondary to an ovarian teratoma following ovarian cystectomy. (10th August 2016) - Tantipalakorn, Charuwan; Soontornpun, Atiwat; Pongsuvareeyakul, Tip; Tongsong, Theera
Abstract : This report is aimed to describe a life-threatening case of anti- N -methyl-d -aspartate receptor (NMDAR) encephalitis secondary to ovarian teratoma with rapid recovery in 1 day after the removal of the tumour. A 23-year-old woman presented with sudden headache, personality changes and seizure. After neurological assessment, limbic or herpes encephalitis was provisionally diagnosed and treated with intravenous immunoglobulin, acyclovir and steroids. The patient had progressive severe neurological symptoms, requiring prolonged intubation and mechanical ventilation. An anti-NMDAR antibody test revealed positive in serum and cerebrospinal fluid at 3 weeks of admission. Pelvic ultrasound examination and CT scan revealed bilateral small ovarian teratomas. Bilateral ovarian cystectomy was performed by open surgery. The patient showed rapid improvement and no longer needed intubation 2 days after the operation. In conclusion, we described a catastrophic case of ovarian teratoma-associated encephalitis with delayed diagnosis but rapid recovery after ovarian cystectomy. This information can probably be helpful to neurologists and gynaecologists.